Genomic exploration of foot-and-mouth disease signal molecules in Malnad Gidda and Hallikar breeds of Karnataka: A RNA-seq approach - SEKAR, YAMINI SRI; SURESH, KURALAYANAPALYA P; SUBRAMANIAM, SARAVANAN; MAMBULLY, SHIJILI; RANI, SWATI; KHATOON, MEHNAJ; CHANDRASEKARAN, DHANUSH; BARMAN, NAGENDRA N; PATIL, SHARANAGOUDA S (The Indian Journal of Animal Sciences, 2024)
Foot-and-mouth disease (FMD) prevails in India, with a notable increase in incidence in Karnataka state. This infectious malady affects various animals characterized by cloven hooves, including cattle breeds crucial to the rural economy of Karnataka, such as Malnad Gidda and Hallikar. The infection of these breeds with the foot-and-mouth disease virus (FMDV) leads to substantial financial losses for the local population. While previous studies have explored these breeds in combination with foreign counterparts, this research emphasizes a separate examination of Malnad Gidda and Hallikar. This study utilized RNA-Seq data and gene expression analysis, and unveiled a total of 588 differentially expressed genes (DEGs) in FMD-infected Malnad Gidda and Hallikar breeds. Among these, 348 genes were overexpressed, while 240 were under-expressed. The DEGs underwent extensive biological, functional enrichment, and pathway analyses using the DAVID tool. The most enriched terms included ‘Defense response to the virus’ (GO:0051607), ‘Identical protein binding’ (GO:0042802), and ‘Pathways of neurodegeneration - multiple diseases.’ In a network-based analysis, ATP5PO, GAPDH, ISG15, MX2, and PSMD14 were identified as the top hub genes among the significant genes. The study uncovered noteworthy findings indicating that the antiviral capabilities of ISG15 and MX2 have been demonstrated in their role against FMDV in both pigs and mice. By delving into the examination of the anti-viral properties of ATP5PO, GAPDH, and PSMD14, the research establishes a foundational platform for future investigations into FMD, offering potential avenues for interventions in the ongoing quest for effective counter measures against the infirmity in Malnad Gidda and Hallikar Breeds.